Groei en ontwikkeling van Friesverse - Olivier, Pieter Jacques (University of the Free State, 1990)
The purpose of this research project was to select which of the following grazing systems would result in the highest qrowth performance for Friesian heifers, i.e. 1 day grazing, 14 days rest (15 days system), 2 days grazing 28 days rest (30 days system) and 4 days grazing 56 days rest (60 days system). Holstein-Friesian heifers between the ages of 6 to 12 months were put on summer kikuyu pastures for two seasons, which included a wetter and drier year. The 15 day grazing system gave significantly better mass gains in both the drier and wetter years than the 30 day and 60 day grazing systems (P ≤ 0.01). In the drier year the only tendency shown was that the 30 day grazing system gave better live mass gains than the 60 day grazing system. Differences were not significant. In the wetter year the 30 day grazing system gave significantly higher mass gains compared to the 60 day grazing system (P ≤ 0.01). Results for shoulder height increases, udder size increases, teat length increases and teat diameter increases varied over the two seasons. In the wetter year the following results were found. The dry matter intake of the 15 day grazing system was significantly higher than that of the 60 day grazing system (P ≤ 0,01). Time spent grazing per day for the 60 day grazing system was significantly longer than the 15 day and 60 day grazing systems (P ≤ 0,01). Serum mineral profiles showed no shortages, as well as no significant differences between treatments. Disc meter data showed that enough food was available for the animals, but that no deductions could be made from this as to what the intake of the animals was. Crude fibre results showed no significant differences between treatments. The total nitrogen analysis showed that the protein content of the grazing on the 15 day cycle was significantly higher than that of the 30 day and 60 day cycle. The general conclusion reached was that short graze and short rest grazing systems on kikuyu would give higher mass gains for Friesian heifers between the ages of 6 to 12 months than longer grazing-rest systems. Supplementary feeding on these pastures is however necessary to obtain the necessary average daily gains.

Die doel van die navorsingsprojek was om te bepaal watter een van die volgende drie weidingstelsels naamlik 1 dag wei 14 dae rus (15 dae stelsel), 2 dae wei 28 dae rus (30 dae stelsel) en 4 dae wei 56 dae rus (60 dae stelsel) die beste groeiprestasies vir Friesverse tot gevolg het. Holstein-Friesverse is tussen die ouderdom van 6 tot 12 maande laat uitgroei op somerkikoejoeweidings vir twee seisoene lank wat 'n natter en droër seisoen ingesluit het. Die 15 dae weidingstelsel het betekenisvol beter liggaamsmassatoenames in die natter en droër jaar as beide die 30 dae en 60 dae weidingstelsels getoon (P ≤ 0.01). In die droër jaar is slegs 'n tendens van beter liggaamsmassatoename van die 30 dae stelsel teenoor 60 dae stelsel waargeneem. Verskille was egter nie betekenisvol nie. In die natter jaar het die 30 dae stelsel betekenisvol beter toenames getoon as die 60 dae stelsel (Pb ≤ 0.01). Resultate vir skofhoogtetoenames, uiergroottetoenames, speenlengtetoenames en speendeursneetoenames was wisselend vir die twee seisoene. Die volgende resultate ten opsigte van die natter jaar is gevind. Droë materiaal innames van die 15 dae stelsel was betekenisvol (P ≤ 0.01) hoër as die van die 60 dae stelsel. Totale wei tyd per dag was vir die 60 dae stelsel die langste (P ≤ 0,01). Serummineraalprofiele het geen tekorte asook geen betekenisvolle verskille tussen behandelings uitgewys nie. Skyf-weiveldmeterresultate het slegs bewys dat genoeg weiding aan die diere beskikbaar was, maar dat geen afleidings ten opsigte van die inname van verse op kikoejoeweidings moontlik is nie. Ruveseldata het gewys dat daar geen betekenisvolle verskille tussen behandelings bestaan nie. Stikstofontledings het aangedui dat die weidings-proteieninhoud van die 15 dae stelsel betekenisvol hoër was as beide die 30 dae en 60 dae stelsels (P ≤ 0.05). Die algemene gevolgtrekking waartoe gekom is, is dat vir Friesverse tussen die ouderdomme van 6 tot 12 maande, kort wei kort russtelsels op kikoejoeweiding hoër liggaamsmassatoenames as langer wei langer russtelsels sal gee. Byvoeding op hierdie weidings is egter nodig om die vereiste gemiddelde daaglikse toenames te verseker.
Dissertation (M.Sc.Agric. (Animal Science))--University of the Free State, 1990
Keywords: Holstein-Friesian cattle -- Growth; Grazing system